A Cross-Sectional Study of Commercial Ewe Management Practices for Different Sheep Breeds across Southern Australia - Amy L. Bates; Shawn R. McGrath; Maxwell B. Allworth; Susan M. Robertson; Gordon Refshauge (Animals, 2023)
The management of ewes across southern Australia may vary with breed and can change over time and, as such, a greater understanding of producer management practices and the motivations that influence these practices is required. A cross-sectional study was performed by telephone interview with sheep producers managing Composite, Maternal, Merino or shedding ewe breeds mated in either spring, summer, or autumn. The surveyed producers were a unique subset of southern Australian producers. A large proportion of the surveyed producers followed current best practice guidelines for ewe mating and lambing nutritional management; however, some producers did not align with these targets. Further, some producers did not see the value in attaining the current recommendations. Pregnancy scanning was widely practiced, likely an artefact of the recruitment process; however, a few producers did not utilize this information for nutritional management at lambing time. Finally, most producers were active in their search for new information, seeking information regularly from a wide range of sources and reported making management changes within the last five years. Further work is required to understand why some producers are not adopting best practice where possible and to understand current barriers for adoption. Management guidelines for all sheep breeds are required to best manage sheep across southern Australia.